EFFECT OF GINGER ON ACETYLCHOLINE ACTIVITY IN BRAIN AND IT'S POSSIBLE ROLE IN LEARNING AND MEMORY DURING ETHANOL WITHDRAWAL - Maralla, Swaroopa; Reddy, K. Sathyavelu (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Alcohol depletes acetylcholine levels in the brain thus accounting for some of the cognitive impairments and withdrawal symptoms associated with alcohol ingestion. Low acetylcholine levels produced by alcohol intake results in long and short term memory deficits, trouble focusing, concentrating as well as stage 4 (REM) sleep deprivation. Methods: Measurements of brain acetylcholine levels and acetylcholine metabolizing enzyme AchE were made in rats treated with either ethanol (2g kg-1 body wt daily) alone or ethanol with ginger extract supplementation (200 mg kg-1 body wt daily for 6 weeks). EtOH with or without ginger extract was administered orally by oral intubation for 42 days. Matched controls were given saline. Results: ACh synthesis in the brain of rats treated with ethanol alone for 6 weeks was significantly (P less than 0.01) inhibited. Ach concentration in the brain of rats treated with ethanol plus ginger extract for 42 days was three times that of rats treated with ethanol alone. ACh synthesis in rats with ethanol withdrawal and ginger extract supplementation was also significantly (P less than 0.01) higher. Spatial memory and learning of rats were tested by Morris water maze test with or without ginger extract supplementation during withdrawal from chronic ethanol consumption was also tested. The effect of EtOH on ACh synthesis and influence of ginger extract on Ach concentration in the brain was found to be positively correlated. Conclusion: The current data suggest that chronic ethanol exposure may decrease ACh synthesis while ginger extract restores and exhibits protective capability and cognitive enhancing properties during ethanol withdrawal. Keywords: Ginger Extract; Alcohol; Cognitive Behaviour; Acetylcholine; Ethanol Withdrawal